Etrasimod as induction and maintenance therapy for ulcerative colitis (ELEVATE): two randomised, double-blind, placebo-controlled, phase 3 studies. Issue 10383 (8th April 2023) - Sandborn, William J; Vermeire, Séverine; Peyrin-Biroulet, Laurent; Dubinsky, Marla C; Panes, Julian; Yarur, Andres; Ritter, Timothy; Baert, Filip; Schreiber, Stefan; Sloan, Sheldon; Cataldi, Fabio; Shan, Kevin; et al.
Summary: Background: Etrasimod, a once-daily, oral, sphingosine 1-phosphate (S1P) receptor modulator that selectively activates S1P receptor subtypes 1, 4, and 5, with no detectable activity on S1P2, 3, is in development for the treatment of immune-mediated diseases, including ulcerative colitis. In these two phase 3 trials, we aimed to evaluate the safety and efficacy of etrasimod in adult patients with moderately to severely active ulcerative colitis. Methods: In two independent randomised, multicentre, double-blind, placebo-controlled, phase 3 trials, ELEVATE UC 52 and ELEVATE UC 12, adults with active moderate-to-severe ulcerative colitis and an inadequate or loss of response or intolerance to at least one approved ulcerative colitis therapy were randomly assigned (2:1) to once-daily oral etrasimod 2 mg or placebo. Patients in ELEVATE UC 52 were enrolled from 315 centres in 40 countries. Patients in ELEVATE UC 12 were enrolled from 407 centres in 37 countries. Randomisation was stratified by previous exposure to biologicals or Janus kinase inhibitor therapy (yes vs no), baseline corticosteroid use (yes vs no), and baseline disease activity (modified Mayo score [MMS]; 4–6 vs 7–9). ELEVATE UC 52 comprised a 12-week induction period followed by a 40-week maintenance period with a treat-through design. ELEVATE UC 12 independently assessed induction at week 12. The primary efficacy endpoints were the proportion of patients with clinical remission at weeks 12 and 52 in ELEVATE UC 52 and week 12 in ELEVATE UC 12. Safety was evaluated in both trials. ELEVATE UC 52 and ELEVATE UC 12 were registered with ClinicalTrials.gov, NCT03945188 and NCT03996369, respectively. Findings: Patients in ELEVATE UC 52 were enrolled between June 13, 2019, and Jan 28, 2021. Patients in ELEVATE UC 12 were enrolled between Sept 15, 2020, and Aug 12, 2021. ELEVATE UC 52 and ELEVATE UC 12 screened 821 patients and 606 patients, respectively, with 433 and 354 subsequently undergoing random assignment. The full analysis set of ELEVATE UC 52 comprised 289 patients assigned to etrasimod and 144 to placebo. In ELEVATE UC 12, 238 patients were assigned to etrasimod and 116 to placebo. In ELEVATE UC 52, a significantly greater proportion of patients in the etrasimod group achieved clinical remission compared with patients in the placebo group at completion of the 12-week induction period (74 [27%] of 274 patients vs ten [7%] of 135 patients; p<0·0001) and at week 52 (88 [32%] of 274 patients vs nine [7%] of 135 patients; p<0·0001). In ELEVATE UC 12, 55 (25%) of 222 patients in the etrasimod group had clinical remission compared with 17 (15%) of 112 patients in the placebo group at the end of the 12-week induction period (p=0·026). Adverse events were reported in 206 (71%) of 289 patients in the etrasimod group and 81 (56%) of 144 patients in the placebo group in ELEVATE UC 52 and 112 (47%) of 238 patients in the etrasimod group and 54 (47%) of 116 patients in the placebo group in ELEVATE UC 12. No deaths or malignancies were reported. Interpretation: Etrasimod was effective and well tolerated as an induction and maintenance therapy in patients with moderately to severely active ulcerative colitis. Etrasimod is a treatment option with a unique combination of attributes that might address the persistent unmet needs of patients with ulcerative colitis. Funding: Arena Pharmaceuticals.